South Africa’s interest rate behaviour: Investigating the influence of the indicators of financial openness - Chile, Nzeh, Innocent; Ogomegbunam, Okolie David; Ibekwe, Okolie Jonathan; Chinedu, Izuogu Augustine (Asian Journal of Economics and Empirical Research, 2023)
This study seeks to investigate the influence of financial openness variables on South Africa’s interest rate during the period between1980-2020. The study used both Augmented Dickey-Fuller (ADF) and Philip-Perron (PP) tests to determine the order of integration of the variables, while the autoregressive distributed lag (ARDL) bounds test was used to investigate both the short and long-run impact of the independent variables on the dependent variable. The findings of the study revealed that in the short-run both foreign direct investment (FDI) inflows and FDI outflows impacted the interest rate positively. However, portfolio investment, exchange rate and capital account openness did not have any significant impact on interest rate within the duration of this research. The long-run results revealed that FDI inflows had a positive and significant impact on interest rate. Also, while capital account openness had a significant and positive impact on the interest rate, FDI outflows, portfolio investment, and the exchange rate had no significant impact on interest rate. The study concludes that apart from portfolio investment which did not exert significant impact on interest rate, other financial openness indicators used in the study had a significant impact on South Africa’s domestic interest rate. The paper argues that, appropriate monetary policy measures targeted to lessen the monetary impact of excess capital inflows should be considered. Additionally, capital account liberalization policy should be encouraged, but it needs to be regulated if it places an excessive amount of liquidity pressure on the economy.